The Benacerraf Problem as a Challenge for Ontic Structural Realism. Issue 1 (31st October 2019) - Beni, Majid Davoody
ABSTRACT: Benacerraf has presented two problems for the philosophy of mathematics. These are the problem of identification and the problem of representation. This paper aims to reconstruct the latter problem and to unpack its undermining bearing on the version of Ontic Structural Realism that frames scientific representations in terms of abstract structures. I argue that the dichotomy between mathematical structures and physical ones cannot be used to address the Benacerraf problem but strengthens it. I conclude by arguing that versions of OSR that do not rely on mathematical frameworks for representational purposes need not be vulnerable to Benacerraf's second problem.